Balancing Progress to Equity: The Philippines’ K-12 Education Digitaliza-tion Transition During Post-Pandemic Recovery - Delos Santos, Danilo Lorenzo S. (International Journal of Multidisciplinary: Applied Business and Education Research, 2025)
The Philippines currently is nestled in its demographic golden age with more Filipinos who are part of the productive working force. With the growing population of the island nation, the expectations of a workforce-centric growth model are expected. It is however still in question if the Philippines can tap into this critical resource in its skill development and quality through its transition to K-12 education standard. With its economy highly reliant on dollar remittances abroad from its abundant overseas workforce, the urgency to maximize its economic value by producing a highly capable and skilled population is highlighted to ensure sustainable growth. To analyze this, innovation policy is studied from the initial years of the K-12 implementation phase to the post-pandemic recovery years of 2020-2022. It will look into the various updates in the education roadmap and how it had an impact on inequality in a post-pandemic recovery.